(untitled) (EAAE Annual Conference Proceedings, 2023)
There is a key point in architectural education that should be clarified to improve the legitimation of architects and urban planners in the digital and global world of today: The relationships between experience and knowledge in architectural and urban design theories and practices. Our proposal refers to the historical seminar in MOMA in 1948 about a similar topic, since it is the definition of modernity related to the old and new Bauhaus experiences that is involved in architectural education today.